A multipixel diffuse correlation spectroscopy system based on a single photon avalanche diode array. Issue 11 (5th August 2019) - Johansson, Johannes D.; Portaluppi, Davide; Buttafava, Mauro; Villa, Federica
Abstract: The autocorrelation of laser speckles from coherent near infrared light is used for noninvasive estimates of relative changes in blood perfusion in techniques such as laser Doppler flowmetry (LDF) and diffuse correlation spectroscopy (DCS). In this study, a 2D array of single photon avalanche diodes (SPADs) was used to combine the strengths of multiple detectors in LDF with high light sensitivity in DCS. The system was tested on milk phantoms with varying detector fiber diameter (200 and 600 μm), source‐detector fiber separation (4.6‐10.2 mm), fiber‐SPAD distance (2.5‐36.5 mm), contiguous measurement time per repetition for the autocorrelation (1‐33 ms) and temperature (15.6‐46.7°C). An in vivo blood occlusion test was also performed. The multipixel approach improved signal‐to‐noise ratio (SNR) and, in our setup, the use of a multimode detector fiber was beneficial for SNR. In conclusion, the multipixel system works, but improvements and further studies regarding, for example, the data acquisition and optimal settings are still needed. Abstract : An array of single photon avalanche diodes was used to combine the strengths of the two blood flow laser speckle techniques: laser Doppler flowmetry and diffuse correlation spectroscopy. The system was tested on milk with varying optical fiber configurations and temperature. Multiple pixels and multiple speckles per pixels both improved signal‐to‐noise ratio in this setup.